Assessment of Beliefs, Behaviors and Attitude about voluntary, non-remunerated blood donation among College going students: A prospective study in a tertiary care medical college from North India - Shailesh Kumar Mishra (Journal of Health Promotion and Behavior, 2024)
Background: Blood services are facing a shortage of blood all over the world. Demand for blood is rising day by day and current blood donation is insufficient to meet the demand. This study aimed to assess college-going student’s beliefs, behaviors and attitude regarding voluntary, non-remunerated blood donation. Subjects and Method: This was a cross-sectional study, conducted in the Department of Transfusion Medicine PGIMER Chandigarh, India, from 2011 to 2013. A total of 1,000 (500 blood donor and 500 non-blood donor students) subjects were selected in this study by random sampling. The data were collected through interviews using questionnaires and analyzed descriptively. Results: Assessment of the level of knowledge among blood donor participant revealed that 36 (7.2%) subjects had excellent knowledge, 222 (44.4%) had good knowledge, 152 (30.4%) had average knowledge, 90 (18%) had poor knowledge. No subjects among blood donor students had a very poor level of knowledge. Among non-blood donor participants 93 (18.6%) had a good level of knowledge, 108 (21.6%) had an average level of knowledge, 166 (33.2%) had a poor level of knowledge, 133 (26.6%) had very poor level of knowledge. Conclusion: Data analysis revealed differences in the knowledge level among the donors and non-blood donor participants.